RANCANG BANGUN DC-DC FLYBACK KONVERTER PADA FUEL CELL MENGGUNAKAN MODE DCM (DISCONTINUOUS CONDUCTION MODE) - Haidar Taqy; Waru Djuriatno; Panca Mudjirahardjo (Jurnal Mahasiswa TEUB, 2023)
Energy is one of the main sources in human daily life, the resources are divided into two part, it is renewable and non-renewable resources. In the 21st century, fuel cells has been known as a technology which can produce electrical energy and heat energy efficiently and cleanly. This fuel cell is a renewable energy category, therefore it will be environmentally friendly. Then, to support the performance of fuel cell, it requires a tool namely DC-DC converter. DC-DC converter is an electronic circuit that is used to increase or decrease the DC voltage value. There are many kind of topologies for this converter, one of them is the flyback topology. The flyback topology is a relatively simple topology than the other topologies, especially for the low power category. In this flyback converter circuit there is a transistor controlled ignition circuit, namely Pulse Width Modulation (PWM). The function of PWM is to compare the DC reference signal waveform with a triangle. There are variation of duty cycle value in the PWM control circuit which is regulated by the Arduino microcontroller. In this converter there is a transfomator to increase the DC voltage valueas it was expected. The sensors used in this flyback converter are current sensors and voltage sensors, in order to display data results accurately. Keywords : Fuel Cell, DC-DC converter, DC Voltage, Flyback, Pulse Width Modulation, Duty Cycle, Transformer, Microcontroller DAFTAR PUSTAKA[1] H. Suhada, “Fuel Cell Sebagai Penghasil Energi Abad 21,” 2001. [Online]. Available: http://puslit.petra.ac.id/journals/mechanical/92[2] “Fuel Cell Handbook (Seventh Edition),” 2004.[3] G. C. Nugroho, T. Andromeda, and Y. Christyono, “PERANCANGAN KONVERTER ARUS SEARAH TIPE FLYBACK SEBAGAI CATUDAYA RANGKAIAN DRIVER DAN MICROCONTROLLER PADA KONVERTER TIPE ZETA,” TRANSIENT, vol. 7, no. 4, p. 897, May 2019, doi:10.14710/transient.7.4.897-903.[4] S. S. Deswal, “Application of Boost Converter for Ride-through Capability of Adjustable Speed Drives during Sag and SwellConditions Biological evaluation of Lagenaria siceraria View project Antiulcer Product Standardization View project.” [Online]. Available: https://www.researchgate.net/publication/242582788[5] B. Rudiyanto, A. Susanto, and Y. Susmiati, “Aplikasi Kontrol PI (Proportional Integral) pada Katup Ekspansi Mesin Pendingin,” 2016. [Online]. Available: http://www.jurnal.unsyiah.ac.id/RTP[6] A. A. Kurniawan, B. Fatkhurrozi, and R. A. Wibowo, “DESAIN FLYBACK CONVERTER MENGGUNAKAN KLEM AKTIF UNTUK SISTEMPHOTOVOLTAIC 500W,” Theta Omega: Journal of Electrical Engineering.[7] S. Noor and N. Saputera, “EFISIENSI PEMAKAIAN DAYA LISTRIK MENGGUNAKAN KAPASITOR BANK,” 2014.